2021
DOI: 10.1038/s41477-021-00930-0
|View full text |Cite
|
Sign up to set email alerts
|

What shoots can teach about theories of plant form

Abstract: Plants generate a large variety of shoot forms with regular geometries. These forms emerge primarily from the activity of a stem cell niche at the shoot tip. Recent efforts have established a theoretical framework of form emergence at the shoot tip, that has empowered the use of modelling hand in hand with biological approaches to start disentangling the biochemical and physical mechanisms canalizing form development at the shoot tip. We discuss here how these advances get us closer to identifying the construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 105 publications
0
7
0
Order By: Relevance
“…We have mentioned in section 2 the fact that mechanical stresses have been proposed to regulate PIN polarities. These mechanical stresses result from the shape of the tissue as well as growth and the changes in shape that can occur during development (For review: (138)). Mechanical stresses, transmitted to neighboring cells and acting on the orientation of microtubules, can explain a flux-based behavior of PIN in both the shoot and root apical meristem (53,82) and robustness of auxin distribution (29).…”
Section: Auxin Cross-talks With Many Hormones and Other Developmental...mentioning
confidence: 99%
“…We have mentioned in section 2 the fact that mechanical stresses have been proposed to regulate PIN polarities. These mechanical stresses result from the shape of the tissue as well as growth and the changes in shape that can occur during development (For review: (138)). Mechanical stresses, transmitted to neighboring cells and acting on the orientation of microtubules, can explain a flux-based behavior of PIN in both the shoot and root apical meristem (53,82) and robustness of auxin distribution (29).…”
Section: Auxin Cross-talks With Many Hormones and Other Developmental...mentioning
confidence: 99%
“…Given that epidermal auxin convergence points were proposed as the trigger for auxin movement into internal cells (Scarpella et al ., 2006), but recent experiments revealed that they are neither necessary or sufficient for midvein formation in Arabidopsis (Govindaraju et al ., 2020; Lavania et al ., 2021), unknown components of auxin flux mechanisms obviously exist. In this context, both experimental and modelling approaches have suggested that mechanical stresses mediated by microtubule and cellulose microfibril dynamics play a role in both UTG and WTF movement of auxin, and it is becoming increasingly clear that the significance of auxin‐driven reorientation of PIN1 proteins during leaf primordium and midvein formation needs to be reevaluated in a more complex framework than previously considered (recently discussed and reviewed in Heisler, 2021; ten Tusscher, 2021; Vernoux et al ., 2021).…”
Section: Ontogeny Of Leaf Veinsmentioning
confidence: 99%
“…The SAM is the source of all cells that ultimately form the above-ground architecture of plants, including the subset that ends up building the leaves ( Vernoux et al, 2021 ). The homeobox gene WUSCHEL ( WUS ), which is specifically expressed in the organizing center of the SAM, plays a central role in the formation and maintenance of the shoot meristem activity ( Schoof et al, 2000 ); loss-of-function mutations in WUS result in the misspecification of stem cells and the premature termination of meristem activity ( Lenhard et al, 2001 ).…”
Section: Leaf Initiationmentioning
confidence: 99%